Srylosanthes mexicana Taub. (Fabaceae) - new to Indian flora - S. C., Srivastava; Ranjan, Vinay (Malaysian Journal of Science, 2010)
Srylosanthes mexicana Taub. (Fabaceae) (Fabaceae) is reported new to Indian flora.